2020
DOI: 10.1002/admi.202000597
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatible Direct Deposition of Functionalized Nanoparticles Using Shrinking Surface Plasmonic Bubble

Abstract: Functionalized nanoparticles (NPs) are the foundation of diverse applications. Especially, in many biosensing applications, concentrating suspended NPs onto a surface without deteriorating their biofunction is usually an inevitable step to improve detection limit, which remains to be a great challenge. In this work, we demonstrate biocompatible deposition of functionalized NPs to optically transparent surfaces using shrinking bubbles. Leveraging the shrinking phase of bubble mitigates the biomolecule degradati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 64 publications
(96 reference statements)
1
27
0
Order By: Relevance
“…Using high-speed videography with interferometry, we indeed observe that the front TPCL is pushed forward when the laser spot overlaps with the front contact line, which sequentially leads to the depinning of the trailing TPCL and eventually leads the bubble to slip forward within ~ 1 ms. This confirms that the TPCL de-pinning due to the plasmonic NPs heating is the main reason for the laser directed surface bubble movement, and the possibility of high-precision bubble manipulation has useful practical implications for a wide range of microfluidic applications [1][2][3][4][5][6][7][8][9][10] .…”
Section: Introductionsupporting
confidence: 60%
See 1 more Smart Citation
“…Using high-speed videography with interferometry, we indeed observe that the front TPCL is pushed forward when the laser spot overlaps with the front contact line, which sequentially leads to the depinning of the trailing TPCL and eventually leads the bubble to slip forward within ~ 1 ms. This confirms that the TPCL de-pinning due to the plasmonic NPs heating is the main reason for the laser directed surface bubble movement, and the possibility of high-precision bubble manipulation has useful practical implications for a wide range of microfluidic applications [1][2][3][4][5][6][7][8][9][10] .…”
Section: Introductionsupporting
confidence: 60%
“…Plasmonic bubbles can be generated in noble metal plasmonic NP suspensions upon the irradiation of a pulsed laser due to the enhanced plasmonic resonance [1][2][3][4][5][6]. These micro-sized bubbles can play important roles in a wide range of applications, including biomedical imaging [7][8][9][10], healthcare diagnosis [11][12][13][14][15], and microfluidic bubble logics [16].…”
Section: Introductionmentioning
confidence: 99%
“…Such nanobubbles can be made of vapor, dissolved gas, or their combinations, and they usually have diameters on the order of several tens to hundreds of nanometers. These nanobubbles are known for their unique photothermal and optical properties and have already led to biomedical applications in cell-level therapy and imaging, controlled drug release and delivery, microtissue surgery, and biosensing, with some already entered into clinical trials. They are also studied for energy and fluidic applications like solar-vapor generation, , plasmon-assisted photocatalytic reactions, optofluidics, nano swimmers, surface bubble manipulation, and materials assembly . In case the plasmonic NPs are immobilized or fabricated on a substrate, they can form bubbles on the surface upon optical excitation, and we refer to them as plasmonic surface bubbles, but our focus in this article is on plasmonic nanobubbles, which are formed around NPs suspended in liquids.…”
Section: Introductionmentioning
confidence: 99%
“…[ 96–105 ] However, a high working temperature required to vaporize water has prevented the optothermally generated microbubbles from being applied to sensing proteins, whose activity is subject to thermal denaturation. [ 95,106 ] Kim et al. reported a biphasic liquid system wherein volatile, water‐immiscible perfluoropentane (PFP) was emulsified into an aqueous medium as a bubble‐generating liquid (Figure 5e).…”
Section: Diffusion‐limit‐breaking Systems For Enhancing Sensor–analytmentioning
confidence: 99%
“…[96][97][98][99][100][101][102][103][104][105] However, a high working temperature required to vaporize water has prevented the optothermally generated microbubbles from being applied to sensing proteins, whose activity is subject to thermal denaturation. [95,106] Kim et al reported a biphasic liquid system wherein volatile, water-immiscible perfluoropentane (PFP) was emulsified into an aqueous medium as a bubble-generating liquid (Figure 5e). [107] With a single protein-protein interaction model (immunoglobulin G as a surface capture molecule and protein A/G as an analyte), one-order-of-magnitude enhancement of surface capture was achieved within 1 min, compared to a static incubation method with an incubation time of 30 min (Figure 5f).…”
Section: Enhanced Analyte-sensor Contact By Analyte Concentratingmentioning
confidence: 99%